A Preliminary Investigation on the Antimicrobial Activity of Listerine®, Its Components, and of Mixtures Thereof. (24th June 2015) - Vlachojannis, C.; Chrubasik‐Hausmann, S.; Hellwig, E.; Al‐Ahmad, A.
<x xml:space="preserve">Abstract</x> Listerine® is one of the most popular mouthwashes worldwide and claims to combat harmful bacteria. In the past century, its recipe was changed from an essential oil mouthwash to a five‐component mixture (thymol, menthol, eucalyptol, and methyl salicylate dissolved in 27% ethanol). The aim of this study was to get preliminary information about the antimicrobial activities of individual Listerine® components and their mixtures. We tested the bacterial strains Streptococcus mutans, Enterococcus faecalis, and Eikenella corrodens and the yeast Candida albicans. The established minimum inhibitory concentration (MIC) assay and the minimum bactericidal/fungicidal concentration (MBC/MFC) assay were applied. None of the combinations of two phenols at the concentrations contained within Listerine® were associated with either an additive or synergistic effect. Thymol had lower MIC and MBC/MFC values than the other Listerine® components and Listerine® against E. corrodens and C. albicans. The mixtures consisting of eucalyptol, methyl salicylate, and thymol were the most effective against S. mutans and E. faecalis and more effective than Listerine®. Our results demonstrate that the phenols and their concentrations as contained within Listerine® could be further optimized in terms of selecting those which increase their general effectiveness, at concentrations that do not induce harm. Copyright © 2015 John Wiley & Sons, Ltd.